Physical and combustion properties of nonwoven fabrics produced from conventional and naturally colored cottons. Issue 16 (October 2015) - Hinchliffe, Doug; Condon, Brian; Delhom, Christopher D; Chang, SeChin; Montalvo, Joseph; Madison, Crista; Reynolds, Michael; VonHoven, Terri; Cintrón, Michael Santiago
A comparative study was conducted to identify the effects of processing on physical and combustion properties of needlepunched (NP) and hydroentangled (H-E) nonwoven fabrics produced from fibers of white fiber cotton and a naturally colored brown fiber cotton. A significantly higher degree of flame retardancy (FR) in was observed in fabrics produced from brown cotton fibers compared with white fibers. Calorimetry revealed lower heat release capacity, lower peak heat release rate, and total heat release from brown fibers compared with white fibers. The ash content was also higher in brown fiber samples suggesting higher levels of inorganic elements in the brown fibers. Elemental analyses revealed brown cotton fibers had higher levels of known FR elements including phosphorous and magnesium. The H-E process reduced FR in brown fabrics, which also correlated with a reduction in phosphorous. However, brown H-E fabrics still maintained higher FR than white H-E fabrics. Water content analysis indicated higher water levels in brown fibers, particularly brown greige fibers, which correlated with increased FR. Processing parameters such as energy of H-E did not affect combustion of the two fabric types. Scouring of the brown fiber fabrics reduced, but did not remove coloration, while scouring and bleaching removed the brown color completely. Scouring alone, or scouring and bleaching, completely removed the higher FR properties of the brown fiber fabrics. The results indicate that the mechanism of FR in brown cotton fibers is dependent on multiple compositional factors that may include element content, water content, and compounds related to coloration.